2017
DOI: 10.1177/0363546517691517
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Reconstruction of the Anterior Cruciate Ligament of the Knee With or Without Reconstruction of the Anterolateral Ligament: A Randomized Clinical Trial

Abstract: Combined ACL and ALL reconstruction was found to be effective in improving subjective and objective outcomes. Nevertheless, these findings were not significantly superior to isolated ACL reconstruction except for the instrumented knee laxity testing results. This might indicate that ALL reconstruction should not be performed routinely for patients undergoing ACL reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
120
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(138 citation statements)
references
References 35 publications
4
120
4
2
Order By: Relevance
“…In this trial, the patients who received the combined procedure had the best IKDC (International Knee Documentation Committee) subjective scores and returned to sports sooner. In 2017, Ibrahim and colleagues 15 reported a trial in which 110 patients with high-grade pivot shifts were allocated by birthdates to receive semitendinosus ACLR with or without the addition of a gracilis ALL reconstruction. The authors found no obvious superiority for the combined procedure other than a mean 0.5-mm advantage in instrumented laxity testing and concluded that the adjunctive ALL reconstruction should not be performed routinely in patients undergoing ACLR.…”
mentioning
confidence: 99%
“…In this trial, the patients who received the combined procedure had the best IKDC (International Knee Documentation Committee) subjective scores and returned to sports sooner. In 2017, Ibrahim and colleagues 15 reported a trial in which 110 patients with high-grade pivot shifts were allocated by birthdates to receive semitendinosus ACLR with or without the addition of a gracilis ALL reconstruction. The authors found no obvious superiority for the combined procedure other than a mean 0.5-mm advantage in instrumented laxity testing and concluded that the adjunctive ALL reconstruction should not be performed routinely in patients undergoing ACLR.…”
mentioning
confidence: 99%
“…There have been attempts to study clinical outcomes of ALL reconstructions; however, these studies had mixed outcomes and were not able to demonstrate the superiority of combined surgery over isolated ACL reconstruction. [24][25][26][27][28] Recently, Ibrahim et al 25 performed a randomized controlled trial in 110 patients with high-grade pivot shift either assigned to undergo combined ACL and ALL reconstruction or isolated ACL reconstruction, and found no significant difference between the two groups in terms of knee stability. However, the study was limited as there was no attempt to analyze the status of the ALL before determination for ALL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…However, long-term results of ALL reconstruction are not known and have not been suggested as a standard procedure with ACL reconstruction. Despite this, additional ALL reconstruction has been recommended in patients with grade III pivot shift or Segond fracture and athletes practicing of sports with pivot movements [32][33][34]. In addition ACL revision, subjective rotational looseness, and Telos value >10 mm are also considered as indicative of ALL reconstruction associated with ACL reconstruction [35].…”
Section: Surgical Indicationsmentioning
confidence: 99%